1986
DOI: 10.2307/3899674
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Total Fecal Collection for Measuring Cattle Forage Intake

Abstract: Conventional digestibility trials with steers were conducted to evahutte relationships between actual forage intake and estimated forage intake using the total fecal collection procedure. Actual forage intake of 6 of the 9 forages fed was not accurately estimated by the widely used technique of dividing total fecal output by forage indigestibility estimated by in vitro procedures. This was because 4811 in vitro digestibility poorly estimated in vivo digestibility of 6 forages. Regression equations based on in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Holechek et al (1986) studied Hereford × Angus yearling steers and found that the standard 48 h incubation procedure of Van Soest and Wine (1967) underestimated true in vivo digestibility of feeds ranging from only 1% for sainfoin (Onobrychis viciae-folia), to 9% for Timothy grass (Phleum pratense) and 13% for silver ) of the experimental diets. Bd = Brachiaria dictyoneura.…”
Section: Resultsmentioning
confidence: 99%
“…Holechek et al (1986) studied Hereford × Angus yearling steers and found that the standard 48 h incubation procedure of Van Soest and Wine (1967) underestimated true in vivo digestibility of feeds ranging from only 1% for sainfoin (Onobrychis viciae-folia), to 9% for Timothy grass (Phleum pratense) and 13% for silver ) of the experimental diets. Bd = Brachiaria dictyoneura.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of the digestibility of the feed ingested by the goats were obtained using in vitro digestion techniques (Tilley & Terry 1963). Digestion of the feed samples with rumen liquor was prolonged to 72 h as recommended by Holechek et al (1986). An extended incubation period was used to avoid underestimation of digestibility in accordance with recommendations by Mertens & Ely (1982).…”
Section: Feeding Behaviour and Composition Of Dietmentioning
confidence: 99%
“…Our study involved only a limited number of feeds and it is quite possible Table 4 results are diet-specific relations that may not be applicable elsewhere. Total fecal nitrogen output has not been used as an indicator of protein status of ruminants grazing on rangelands; however, it can be evaluated through either total fecal collection (Stallcup et al 1975, Holechek et al 1986 or through external markers (Pond et al 1987). Total fecal nitrogen output may have potential as a future measure of grazing ruminant protein status.…”
Section: Evaluation Of Nitrogen Statusmentioning
confidence: 99%